Efficiency assessment of transport manufacturing firms using a stochastic frontier analysis approach - Ammar Fikree Mohamed Jofree,; Norayati Hashim,; Mohd Fahmy-Abdullah,; Lai, Wei Sieng; Sulhi Ridzuan, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This paper aims to analyze the level of technical efficiency and determinants of technical inefficiency of transport manufacturing firms in Malaysia using Stochastic Frontier Analysis (SFA) approach from 2005 to 2010. Through SFA approach, hypothesis test is conducted in order to select Cobb-Douglas or Translog production function and testing the effects of technical inefficiencies. While the determining factors that been taken into account include the capital-labor ratio, training expenses, education level ratio, wage rate, information and communication technology expenditure, and firm size. Hypothesis test results show that the Cobb-Douglas production function is rejected. While the test for the effect of technical inefficiency shows its existence. Training expenses, secondary and tertiary education level ratios, wage rates and information and communication technology expenses are significant determinants for transportation manufacturing firms. However, the capital-labor ratio was found that it has reduced the level of technical efficiency. The implications of these results show that firms need to focus on investing in human capital, information technology and increase motivation among employees such as rising wage rates and reducing the use of capital appropriate to the technology.